Development of Local Resources for Rural Communities Based on Sustainable Livelihoods to Improve Farmers' Welfare in Enrekang Regency - Irmayani, Irmayani; Arman, Arman; Azis, Dina Aprianty; Amir, Muh. (Agrikan: Jurnal Agribisnis Perikanan, 2022)
Specific objectives are: 1). Formulate and develop a sustainable livelihood-based farmer welfare development model to improve the quality of rural farmers' resources. 2). Applying an integrated pattern between all livelihood concepts, namely the use of natural resources, the availability of human resources, the availability of physical resources, the ability to access financing, and the internalization of social capital in the lives of rural communities in Bone-Bone village. Rural farmers in Bone-Bone village are the population in this study, some of which will be selected as the main samples in this study. The sample used in this study used snowball sampling with data triangulation techniques, by determining key informants in advance, including several leaders or figures in this village community. Rural farmers with the scope of agricultural life which is the color of their daily life so that they are expected to be able to make farmers survive, organize their agricultural life into a mainstay commodity and prosper their lives. The interaction between local economic institutions and market intervention institutions has brought changes to the local economic institutional order, where subsistence ethics is still a moral requirement, but does not provide opportunities for farmers to improve welfare. Even the workings of market institutional mechanisms during the economic crisis have increased the gap between layers of farming society.